1988
DOI: 10.1530/jrf.0.0820277
|View full text |Cite
|
Sign up to set email alerts
|

Influence of melatonin on the testicular regression induced by subcutaneous testosterone pellets in male rats kept in long or short photoperiod

Abstract: Daily afternoon injections of 25 micrograms melatonin for 12 weeks had no effect on testicular weights of male rats kept in long photoperiod (14L:10D); similarly, exposure of rats to short photoperiod (2L:22D) had no effect on gonadal weight. However, rats maintained in a long or short photoperiod and implanted every 2 weeks with a 15 mm Silastic pellet containing testosterone showed a significant reduction in testicular weight; this effect was more pronounced in rats exposed to a short photoperiod. Melatonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Testosterone-primed rats acted like hamsters under a short-day lighting schedule [10,11]. The authors concluded that in the rat the mechanism for regulating photoperiodicity exists but that it is masked by other regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone-primed rats acted like hamsters under a short-day lighting schedule [10,11]. The authors concluded that in the rat the mechanism for regulating photoperiodicity exists but that it is masked by other regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to sensitize the reproductive system of the rat with different procedures, e.g. early adminis tration of testosterone [8], olfactory bulbectomy plus blinding [9], by implanting testosterone pellets to intact rats [10,11], with the result that under continuous darkness (blinded animals) or short photoperiod the gonads regress. The regression can be prevented by pinealectomy [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study melatonin was introduced as a single injection in the afternoon each day for one week. It has been shown earlier that melatonin injections (25-50 pg) given at 16:00 h can induce the short-day effect on the gonadal axis of hamsters (Tamarkin et al, 1976) and rats (Vaughan et al, 1988), indicating that the physiological effect of melatonin can be achieved by this dose and by this method of administration.…”
Section: Discussionmentioning
confidence: 85%
“…Under constant light a low daily dose (125 pg) of testosterone could decrease the serum LH concentration of castrated rats to the level of intact rats, whereas under periodic light a high dose (250 pg) was needed (Porkka-Heiskanen et al, 1989). We wanted to determine whether this sensitization was due to lack of melatonin under constant light, since there is evidence that the increase in testosterone sensitivity associated with photoperiodicity is mediated by pineal melatonin (Ando et al, 1986;Vaughan et al, 1988). We have shown earlier that daily melatonin injections of 50 pg, administered at 09:00 h or 16:00 h to intact or castrated rats do not modulate the secretion of gonadotrophins under periodic or constant light (Porkka-Heiskanen et al, 1990), but the possibility remained that melatonin might prevent the increase in testosterone sensitivity induced by constant light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation